Changes in Movement Coordination Associated With Skill Acquisition in Baseball Batting: Freezing/Freeing Degrees of Freedom and Functional Variability - Gray, Rob (Frontiers in Psychology, 2020)
How do baseball batters solve the problem of coordinating the timing of the different phases of movement to generate a powerful swing that is appropriately adjusted for the trajectory of the pitch? How does the development of this coordination solution depend on the structure of practice? Previously unpublished ground reaction force (GRF) data were analysed to investigate the swing coordination changes that were associated with the changes in batting performance found in the training study by Gray (2017). From pre-post training, there were significant increases in the magnitude of correlations between adjacent swing phases, significant increases in good variability (changes that keep the swing within the required temporal constraint), significant decreases in bad variability (changes that move the swing outside the temporal constraint), and stronger evidence of online adjustments of the different swing phases. These effects were significantly larger for the virtual environment (VE) Adaptive group from the Gray (2017) study that had higher variability in practice conditions. Across all participants, there were significant correlations between the changes in good and bad variability from pre-post training and measures of batting from VE and real hitting tests, and a statistics from league play. These findings suggest that baseball batters solve the problem of coordination by developing functional variability and coupling between swing phases (Katsumata, 2007) which can be facilitated by having more variability in practice conditions.